Techniques of proprioceptive evaluation of the anterior cruciate knee ligament - Alonso, Angélica Castilho; Brech, Guilherme Carlos; Greve, Julia Maria D’Andréa (Acta Fisiátrica, 2010)
The increasing interest in sports activities, combined with the knee’s anatomical vulnerability and complexity, justifies the increasing number of patients with ligament injuries, especially the anterior cruciate ligament (ACL). What then would be the best way to evaluate the knee proprioception? The objective of this study was to identify the techniques of proprioceptive evaluation of the anterior cruciate knee ligament (ACL), and to determine whether a better technique is available. The method was to review the literature, including only those studies published in indexed scientific journals that referred to evaluation tools and/or knee proprioception measurement. The discussion of the different methods of evaluating ACL proprioception, according to the literature, included: morphological anatomical studies; neurophysiologic evaluation, and clinical evaluation which was divided into three types: a) sense of static position; b) kinesthetic posture; and c) postural balance. Although proprioception is important to the final results of a treatment involving ligament injury, its evaluation is still a problem. The conclusion was that the ideal method should have high sensitivity and specificity, in addition to good reproducibility and accuracy. There is lack of consensus in literature regarding the best evaluation technique and the results are also contradictory, despite the balance evaluation being a modern technique used in major research centers, it was not possible to isolate the proprioceptive system from other systems: visual and vestibular.